Barron's profiles of American colleges 2007 (Barron’s Educational Series, Inc., 2007)
"Barron's Profiles of American Colleges 2007" (1656 pages) is divided up in several sections. The first part brings a listing of which majors are provided by what colleges. This was a very handy tool for my daughter, who has very specific ideas as to what majors she is interested in. This section also ranks the colleges in competitiveness/exclusivity (going from "Most Competitive" to "Highly Competitive" etc. all the way down to "Noncompetitive". After that the book brings an overview, thankfully state-by-state, about 1700 colleges